Freight road transport analysis in the metro São Paulo: Logistical activities and CO2 emissions. (July 2020) - Pérez-Martínez, P.J.; Miranda, R.M.; Andrade, M.F.
Graphical abstract: Highlights: This research presents an exhaustive assessment of urban freight in São Paulo. Indicators provide a baseline for assessing trends in freight efficiency over time. This paper has potential significant impact on other Latin-American cities. This study provides tools to complement global emission inventories in urban areas. Results provide freight metrics to Brazil's National Determined Commitments (NDC). Abstract: On-road freight transportation predominates in in the Metropolitan Region of São Paulo (MRSP), railways and other means of transportation do not have the same importance, being is responsible for around a large quantity greenhouse gases (GHGs) emissions. This manuscript presents an assessment of urban road freight in the MRSP based on primary metrics carried out by the Municipality's survey in 2016 on light- and heavy-duty vehicles (LDVs and HDVs). Origin (O) and destination (D) freight activity indicators provide a baseline for assessing trends in efficiency and operational performance. These descriptive (DIs) and key performance indicators (KPIs) come directly and indirectly from the O and D company vehicle survey and identify space and temporal distributions of main freight transport sources by vehicle and commodity types. This paper addresses the need to use the vehicle survey to understand road freight activity and transportation in MRSP and with successive editions of the freight survey it will be possible to track the development of the commodity's transport content to reveal a chronological development in freight logistics and emissions. As the metropolitan region sprawls, it is important to track these metrics in order to define and evaluate sound measures and policies to improve life and air quality. Assumptions and analyses of freight road transport in São Paulo find significant new perspectives to handle several issues in order to assess and improve vehicle utilization, fuel efficiency and CO2 emissions in future over time. This research has potential significant impact in other Latin American cities and the results can be extrapolated to other local freight inventories and be used to provide freight metrics to be included in Brazil's National Determined Commitments (NDC).